Comparison of four treatment regimens for vitiligo in children. - Uksal, U.; Borlu, M.; Atasavun, C.; Ferahbas, A. (European Journal of Pediatric Dermatology, 2002)
It is believed that none of the partially effective treatments are appropriate for children with vitiligo. Initial steps are sunscreens and cover-up, and next, topical corticosteroids, topical or oral psoralens, calcipotriol and/UVR, narrow-band UVB. We clinically evaluated 34 children with vitiligo, -20F, 14M, whose age ranged between 4 and 16-, and examined the association with other autoimmune diseases. Results of four treatment methods - topical bethamethasone, topical calcipotriol, topical psoralen plus sun exposure and narrow- band UVB therapies- were compared. Family history of vitiligo was present in 12 patients (35%). Ten patients had focal, 11 patients segmental and 13 patients generalized type vitiligo. Poliosis, halo nevi, atopic dermatitis and diabetes mellitus type-I were associated diseases. Topical agents were used in focal and segmental vitiligo; generalized cases were treated with narrow-band UVB. Topical bethamethasone group showed repigmentation in 3/11 (27%) cases, calcipotriol group showed repigmentation in 1/10 (10%) cases. There was no satisfactory response in topical psoralen plus sunbath group. Narrow band UVB group showed follicular repigmentation in 7/13 (53%) cases without any side effect at the end of three months.